Study of anaemia profile in a tertiary care hospital in Karnataka, India - Patil, Appu (International Journal of Advances in Medicine, 2020)
Background: Anaemia is a major public health problem worldwide especially in developing countries like India. Nutritional cause of anaemia continues to predominate as the most common cause of anaemia. Objective of this study is to determine the clinical and laboratory profile of anaemia among patients admitted to our hospital. Methods: Our study was a prospective study in which thirty nine patients of anemia admitted to Medicine ward in SNMC and HSK hospital were studied for their clinical and laboratory characteristics. Duration of the study was 7 months from July 2019 to January 2020. Results: Anaemia was more common among females (65.1% of total patients). Patients aged less than 60 years contributed to 85% of patients. Pallor was the universal finding present in 100% of patients. On systemic examination haemic murmurs on auscultation was the most common finding present in 28.2% followed by hepatomegaly (17.94%). Microcytic and dimorphic anaemia constitute the bulk of anaemia. Conclusions: Nutritional anaemia particularly iron deficiency anaemia is the most common cause of anaemia. It tends to affect the working age group and females predominantly. Patients continue to present with severe anaemia to the hospital.